Endoscopic Management of Foreign Bodies in the Gastrointestinal Tract: A Review of the Literature - Mikhael Bekkerman; Amit H. Sachdev; Javier Andrade; Yitzhak Twersky; Shahzad Iqbal (Gastroenterology Research and Practice)
Foreign body ingestion is a common diagnosis that presents in emergency departments throughout the world. Distinct foreign bodies predispose to particular locations of impaction in the gastrointestinal tract, commonly meat boluses in the esophagus above a preexisting esophageal stricture or ring in adults and coins in children. Several other groups are at high risk of foreign body impaction, mentally handicapped individuals or those with psychiatric illness, abusers of drugs or alcohol, and the geriatric population. Patients with foreign body ingestion typically present with odynophagia, dysphagia, sensation of having an object stuck, chest pain, and nausea/vomiting. The majority of foreign bodies pass through the digestive system spontaneously without causing any harm, symptoms, or necessitating any further intervention. A well-documented clinical history and thorough physical exam is critical in making the diagnosis, if additional modalities are needed, a CT scan and diagnostic endoscopy are generally the preferred modalities. Various tools can be used to remove foreign bodies, and endoscopic treatment is safe and effective if performed by a skilled endoscopist.